WORKSHOP DAN BIMBINGAN BERKELANJUTAN PADA K3S UNTUK MENINGKATKAN KEMAMPUAN KEPALA SD DALAM PENGELOLAAN ADMINISTRASI SEKOLAH - Sabitin, Dwi Barniati (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
The problem in this research is the low ability of the principal in managing school administration. This is evidenced by the incomplete documentation of school administration management by 8 elementary school principals in the Wijaya Kusuma Cluster, Ngaliyan District. The aim of the study was to improve the ability of the principal in the Wijaya Kusuma Cluster, Ngaliyan District, in managing school administration. The research subjects were 8 elementary school principals in the Wijaya Kusuma Cluster, Ngaliyan District. This research was conducted in two cycles. Methods of data collection using observation and documentation techniques. Data analysis was carried out by comparing the results in the initial conditions, the results of the first cycle, the results of the second cycle. The results of the study show that: (1) The model for fostering the ability of elementary school principals in managing school administration through Workshops and Continuous Guidance on K3S has proven to be able to improve the ability of elementary school principals in managing school administration in the Wijaya Kusuma Cluster, Ngaliyan District, (2) This can be seen in the results The results obtained, namely from the initial conditions as many as 8 elementary school principals were declared unable to manage administration with a B value with an average rating of 47.4, increased to 2 elementary school principals or 25.00% in the first cycle with an average score of 66, 7 and 100% in the second cycle with an average score of 89.8. The explanation of the value criteria from the initial condition is LESS, increased to ENOUGH and GOOD in the last cycle.